1993
DOI: 10.1093/oxfordjournals.humrep.a138123
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a gonadotrophin-releasing hormone agonist on treatment with low dose follicle stimulating hormone in polycystic ovary syndrome

Abstract: The objective of this study was to investigate whether the incidence of monofollicular growth during stimulation with low dose follicle stimulating hormone (FSH) changes when adjuvant gonadotrophin-releasing hormone agonist (GnRHa) pre-treatment is administered in polycystic ovary syndrome (PCOS). One group of patients (group 1) suffering from clomiphene resistant PCOS was stimulated with low dose FSH. The results were compared with those from another group of similar patients (group 2) subsequently stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…It should be noted that another study, in which PCOS patients received low-dose intravenous pulsatile p-FSH with or without a shorter GnRH-a suppression (3 weeks prior to initiation of p-FSH), failed to show significant differences between groups in urinary oestrogen excretion prior to hCG administration, but reported a higher percentage of multifollicular cycles in the GnRH-a group [28].…”
Section: Discussionmentioning
confidence: 95%
“…It should be noted that another study, in which PCOS patients received low-dose intravenous pulsatile p-FSH with or without a shorter GnRH-a suppression (3 weeks prior to initiation of p-FSH), failed to show significant differences between groups in urinary oestrogen excretion prior to hCG administration, but reported a higher percentage of multifollicular cycles in the GnRH-a group [28].…”
Section: Discussionmentioning
confidence: 95%
“…Although earlier data regarding ovulation and pregnancy rates using the GnRH agonists in FSH-treated cycles were encouraging (Fleming et al 1985 ;Dodson et al 1987 ), subsequent studies demonstrated an increased risk of OHSS (Homburg et al 1990 ;Scheele et al 1993 ;van der Meer et al 1996 ). Although earlier data regarding ovulation and pregnancy rates using the GnRH agonists in FSH-treated cycles were encouraging (Fleming et al 1985 ;Dodson et al 1987 ), subsequent studies demonstrated an increased risk of OHSS (Homburg et al 1990 ;Scheele et al 1993 ;van der Meer et al 1996 ).…”
Section: Ivf/icsi Treatment In Pcosmentioning
confidence: 99%
“…Si ce traitement n'est pas devenu le gold standard, c'est que l'utilisation des analogues de la GnRH alourdit considérablement les traitements, nécessite une dose plus importante de FSH pendant plus longtemps et surtout aboutit plus souvent à une stimulation multifolliculaire responsable d'annulation, d'HSO et de grossesses multiples [247,248]. Dans une étude sur l'induction de l'ovulation en protocole chronic low dose chez des patientes SOPK, Scheele a comparé les stimulations avec et sans analogues de la GnRH [249]. L'utilisation d'analogues s'est soldée par un taux très faible de stimulation monofolliculaire (14 %) par rapport au groupe avec gonadotrophines seules (44 %).…”
Section: Agonistes De Gnrhunclassified